Pendekatan pembelajaran kreatif dan Islami dalam dunia pendidikan - Harlinda Indah (Jurnal Pendidikan Agama Islam, 2026)
This research discusses the Creative and Islamic Learning Approach in the World of Education, aiming to describe the concept and model of creative and Islamic learning in the learning process. This research uses a qualitative method with a literature study approach (Library Research) which focuses on the study of various written sources such as books, scientific journals, articles, and relevant supporting documents. The results of the study show that. Keywords: Islamic Education, Dutch Colonial, Islamic Boarding School, Resistance, Politics of Education. The creative learning approach is a strategy that places students as active subjects in building knowledge through critical, imaginative, and innovative thinking. This approach provides space for learners to develop ideas, find alternative solutions, and relate learning to real experiences. Teachers act as facilitators who create a learning environment that supports exploration, collaboration, and freedom of thought. In the perspective of Islamic education, this approach not only develops intellectual abilities, but also shapes character and morals through the internalization of the values of honesty, responsibility, discipline, and social concern. The integration of creativity and Islamic values makes learning balanced between the intellectual and spiritual aspects. Its implementation can be done through Project-Based Learning, Discovery Learning, Contextual Teaching and Learning, and Cooperative Learning which emphasizes the activeness of students. Overall, this approach improves the ability to think at a higher level while forming a generation with good morals, competitiveness, and balanced personality in the context of 21st-century education and strengthening the nation's character that is sustainable and based on consistent Islamic values.